The Effect of Tax Incentives, Tax Rates and Tax Services on Msmes Taxpayer Compliance in the Midst of the Covid-19 Pandemic in Manado City - SENGKEY, Ribka Alfina Aprilia; RUNTU, Treesje; TANGKUMAN, Steven Josia (PT Keberlanjutan Strategis Indonesia, 2023)
The COVID-19 pandemic has struck around the globe, including Indonesia. The COVID-19 pandemic has had a major impact on economic stability and reduced community productivity, especially for Micro, Small and Medium Enterprises (MSMEs). So that the Government of the Republic of Indonesia through the Ministry of Finance provides tax incentive in an effort to encourage the National Economic Recovery program in the midst of the COVID-19 pandemic. The final Income Tax incentive is a facility for MSMEs taxpayers Borne by the Government. This study aims to determine the effect of tax incentives, tax rates and tax services on MSMEs taxpayer compliance in the midst of the COVID-19 pandemic in Manado City. The research method used in this study is to use quantitative research methods. Sampling technique used in this study is to use purposive sampling and calculated by slovin formula that produces a sample of 100 respondents. Data collection techniques used in this study is using questionnaires. Data analysis techniques used in this study are data quality test, classical assumption test, multiple linear regression analysis and hypothesis test using IBM SPSS Statistics version 25.0 for Windows software. The results of this study indicate that (1) tax incentives do not affect the compliance of MSMEs taxpayers (2) tax rates do not affect the compliance of MSMEs taxpayers, (3) tax services affect the compliance of MSMEs taxpayers, and (4) tax incentives, tax rates and tax services affect the compliance of MSMEs taxpayers.